Inferring the contribution of sexual reproduction, migration and off‐season survival to the temporal maintenance of microbial populations: a case study on the wheat fungal pathogen Puccinia striiformis f.sp. tritici. Issue 3 (20th January 2014) - Ali, Sajid; Gladieux, Pierre; Rahman, Hidayatur; Saqib, Muhammad S.; Fiaz, Muhammad; Ahmad, Habib; Leconte, Marc; Gautier, Angélique; Justesen, Annemarie F.; Hovmøller, Mogens S.; Enjalbert, Jérôme; de, Claude
Abstract Understanding the mode of temporal maintenance of plant pathogens is an important domain of microbial ecology research. Due to the inconspicuous nature of microbes, their temporal maintenance cannot be studied directly through tracking individuals and their progeny. Here, we suggest a series of population genetic analyses on molecular marker variation in temporally spaced samples to infer about the relative contribution of sexual reproduction, off‐season survival and migration to the temporal maintenance of pathogen populations. We used the proposed approach to investigate the temporal maintenance of wheat yellow rust pathogen, Puccinia striiformis f.sp. tritici (PST), in the Himalayan region of Pakistan. Multilocus microsatellite genotyping of PST isolates revealed high genotypic diversity and recombinant population structure across all locations, confirming the existence of sexual reproduction in this region. The genotypes were assigned to four genetic groups, revealing a clear differentiation between zones with and without Berberis spp., the alternate host of PST, with an additional subdivision within the Berberis zone. The lack of any differentiation between samples across two sampling years, and the very infrequent resampling of multilocus genotypes over years at a given location was consistent with limited over‐year clonal survival, and a limited genetic drift. The off‐season oversummering population in the Berberis zone, likely to be maintained locally, served as a source of migrants contributing to the temporal maintenance in the non‐Berberis zone. Our study hence demonstrated the contribution of both sexual recombination and off‐season oversummering survival to the temporal maintenance of the pathogen. These new insights into the population biology of PST highlight the general usefulness of the analytical approach proposed.